THE RELATIONSHIP BETWEEN SELF-CARE MANAGEMENT AND DECLINING OF BLOOD PRESSURE AMONG HYPERTENSIVE PATIENTS IN SUKAMAKMUR COMMUNITY HEALTH CENTER ACEH BESAR - Durratulhikmah; Fauziah; Nurul Amna (PT. Jurnal Center Indonesia Publisher, 2025)
Hypertension is a non-communicable disease indicated by high blood pressure above 140/90 mmHg. This condition leads to major complications if treatment is not received. As a result, managing health is essential to control hypertension. The study aims to investigate the relationship between self-care and the decrease in blood pressure among hypertensive patients in Sukamakmur Public Health Center. The population was 110 hypertensive patients, and 86 respondents were selected as the sample using a random sampling technique. The research was conducted from 15 to 21 April 2025. A quantitative correlational research design was used with a cross-sectional approach. The research instruments were the Hypertension Self-Management Behavior Questionnaire (HSMBQ) and blood pressure assessed using a digital sphygmomanometer. The data that was analyzed from the Chi-Square test analysis showed a p-value of 0.020 (p<0.05). This finding indicated a relationship between self-care management and blood pressure decline in hypertensive patients at the Sukamakmur Community Health Center. This study suggests that patients should be more active and consistently do self-care management to help maintain stable blood pressure levels.